Application of UARS satellite measurements for investigation of wind variations in the upper atmosphere - S. G. Pilipenko (Вісник Астрономічної школи, 2013)
In this work we investigated the change of dynamics of the upper atmosphere over hurricanes. We studied characteristics of the horizontal component of the wind speed within 80–300 km range of altitudes. We analyzed data obtained in 1994 by WINDI (Wind Imaging Interferometer) onboard UARS satellite for hurricane intensities of 4 and 5 points by Saffir–Simpson scale [9]. We plotted the distributions of the zonal and meridional velocity components on height. We found an increase of wind dynamics over strong tropospheric perturbations for altitudes up to 108 km. Acoustic-gravity waves (AGW) may be responsible for propagation of perturbations from the troposphere up, therefore we made a numerical modeling of fluctuations of the vertical and horizontal velocity components when AGW are present in the atmosphere. Moreover, we studied changes of the velocity components due to variation of wave period and horizontal wave number and considered spatial scales of such changes as well.